2016
DOI: 10.1161/hypertensionaha.116.07494
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Variability in Blood Pressure Is Related to Late-Life Cognitive Decline

Abstract: The association between visit-to-visit variability of blood pressure (BP) and cognitive decline over time remains incompletely understood in a general population of older adults. We assessed the hypothesis that higher visit-to-visit variability in BP, but not mean BP, would be associated with faster decline in cognitive function among community-dwelling older adults. This prospective cohort study comprised 976 adults who had 3 or 4 visits with BP measurements as part of the China Health and Nutrition Survey fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 33 publications
8
48
1
Order By: Relevance
“…These measures have been used in previous studies of BP variability 13, 14, 15, 16, 17, 18. Average real variability (ARV) is the average absolute difference between successive BP measurements and, in contrast with SD and CV, it takes into account the order of the clinic visits at which BP was measured 19, 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These measures have been used in previous studies of BP variability 13, 14, 15, 16, 17, 18. Average real variability (ARV) is the average absolute difference between successive BP measurements and, in contrast with SD and CV, it takes into account the order of the clinic visits at which BP was measured 19, 20.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to BP levels, BP variability may be associated with cognitive function 12, 13, 14, 15, 16, 17, 18. BP variability consists of short‐term BP variability (eg, within 24 hours) and long‐term BP variability (eg, visit‐to‐visit BP variability) 19, 20.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Far from being a background noise or a phenomenon occurring at random and able to dilute the prognostic value of the average BP measurements, the BP variability (BPV) is increasingly recognized as a causative factor of the alterations in brain structure and function . In the recent years, a growing evidence about the role of the BPV on the onset and course of cognitive impairment and dementia has become available: several cross‐sectional and longitudinal, prospective cohort studies have clearly demonstrated that increased daytime, day‐to‐day and visit‐to‐visit BP oscillations are significantly associated, independently of average and absolute BP levels, with the cognitive dysfunction both in non‐demented and demented patients, and are independent risk factors for the incidence of cognitive impairment and dementia, including Alzheimer's disease and vascular dementia, and the progression of the neuropsychological decline …”
Section: Blood Pressure Variability: a Novel Vascular Risk Factormentioning
confidence: 99%
“…13 In the current study, we confirmed the importance of residual individual BP variability, which was the only associated with the reduction of cognitive function assessed by MMSE. 4,5,7,15 However, the agreement is lacking because the Honolulu-Asia Aging Study revealed that SBP ≥ 160 mm Hg was related with 51% lower odds of poor performance on a test of global cognition compared with SBP < 100 mm This suggests that BP variability impacts both sexes and that sex hormones do not have protective or adverse effect on cognitive function.…”
Section: Re Sultsmentioning
confidence: 99%